(untitled) (Journal of Comparative & International Higher Education, 2022)
The COVID-19 pandemic upended the Education Abroad (EA) field when in-person programming and travel became impossible. In order to continue offering international experiences to students, many universities and organizations developed virtual EA offerings (VEA). This article presents data from a study that examined educators’ experiences creating, facilitating, and administering these programs through a qualitative survey and optional follow-up semi-structured interview. Including the reflections of 51 EA practitioners, the data reveal positive outcomes and strong support for the continuation of VEA even post-pandemic; the implications of this research are that VEA is an important part of an EA organization’s portfolio and merits additional research. Using Sahin’s application of Rogers’ Theory of Diffusion of Innovations on incorporating technology into education, this paper considers what stage EA stakeholders are at now in the process of accepting the use of the virtual space in the field.